Aprovechamiento de los residuos sólidos y líquidos de faenamiento del camal municipal y su incidencia en la disminución de la contaminación del río tejar del cantón Otavalo. - Yacelga Pastillo, Sonia Magdalena (2014)
The general purpose of this research was to take advantage of blood residues and ruminal content from the slaughter processes in the municipal slaughterhouse of Otavalo, through the design of an alternative treatment to reduce contamination of the Tejar River. In the municipal slaughterhouse, during the activities of slaughtering bovine cattle, organic waste is generated, in greater quantity blood and ruminal content, the same that generate wastewater that is discharged into the Tejar River, a situation that represents an evident environmental damage, and a great waste of resources that can be used or taken advantage of.